Efficacy of a Hypocaloric Mediterranean Diet in Overweight Patients: Factors Predictive of Completion - LT Casañas-Quintana; I Bautista-Castaño; L Serra-Majem (International Journal of Nutrition, 2016)
Objectives: To evaluate the efficacy of a weight loss programme and the factors that predict successful adherence of the treatment. Methodology: A retrospective chart review of 500 overweight outpatients (427 women, 73 men), mean age 41.7 years (range: 18–81) and mean BMI of 31.44 kg/m2 (range: 25.09–51.33), treated at an obesity specific clinic. A programme involving a hypocaloric Mediterranean diet was prescribed, along with suggestions for leisure exercise and daily activity. The weekly follow-up continued until the weight loss goal was reached (‘completion’ group) or the patient discontinued the programme (‘dropout’ group). Key Results: Those that completed the programme achieved a mean weight loss of 10.6 kg (12.9% percentage loss of initial body weight) and a mean body fat mass loss of 26.8%. Factors predictive of completion were: gender (males higher completion), previous dietary programmes (predictive of dropout), initial percentage of fat mass (higher percentage, lower completion), age (younger age, lower completion) and hypothyroid disease (predictive of dropout). Conclusions: A hypocaloric Mediterranean diet and moderate exercise could help to reduce body weight and body fat in overweight patients. Treatment completion of self-selected and self-paying patients is low, and appear to be more effective for men, persons with a low percentage of fat mass, older age groups and those who have not made other previous diets.
Keywords: Obesity